Formasi Berkelanjutan: Membermaknakan Kekinian Imamat - Edison R.L. Tinambunan (Studia Philosophica et Theologica, 2021)
To be a priest, a candidate should study philosophy and theology for more or less seven years of duration which is called Initial Formation, which emphasize four dimensions, which are human being, spiritual, intellectual and pastoral. These dimensions are built up at formation house and college. If Initial Formation is passed through, the candidate is anointed to be a priest and he is ready as in persona Christi for pastoral service who has responsibility and duty in the church and the world. For this service, the priest needs a formation for long his priesthood which is called Ongoing Formation. The dimension which is emphasized at Initial Formation is also given in his priesthood with contents combined by pastoral service and stages of priest, which are junior, middle ages, advanced years and retired or sick. The intention of Ongoing Formation is to support the priesthood for the long life of a priest in order to always embody him with the Great Pastor in life and pastoral service.